Modular DAB DC-DC converter low voltage side dc link capacitor two-stage charging-up control for solid state transformer application - Cao, Shuyu (2018)
This paper presents an effective two stage DAB charging-up control method for modular DC-DC converters with low voltage side common DC bus voltage starting from zero. In 1st stage of charging, the DAB controller is modified to allow variable duty cycle control of medium voltage side DAB converter. In this stage, a constant charging-up current is applied so that low voltage side DC link voltage is charged up linearly. In the 2nd stage of charging control, the normal dual voltage and current control loops are applied. At the end of 2nd charging up stage, the DAB controller is ready for normal power regulation. The proposed DAB charging control method is applicable for modular SST start-up application for both grid tied and standalone application. The important advantage of the proposed DAB charging control method is that the DC-DC converter performance is robust to DC-DC converter circuit parameter variation and operation condition variation among DAB modules. Another attractive advantage is that the proposed solution is purely DAB control algorithm change without requiring extra circuit component in start-up charging process.